Birth Order Effects in the Developed and Developing World: Evidence from International Test Scores - Dana C. Andersen; Pinar Mine Gunes (Institute of Labor Economics (IZA), 2023)
This paper examines the effect of birth order and family size on human capital using a consistent measure of cognitive skills across a diverse set of countries with different levels of development from PISA dataset. Using a birth order index that is orthogonal to family size, as well as controlling for student and family covariates, we find negative family size and birthorder effects in both developed and developing countries. Moreover, estimating the effects by country, there is no evidence of a relationship between birth order effects and the level of development, while the effect of family size is slightly higher in developing countries. The results also show that birth order effects are declining in birth order and that birth order matters more among smaller families than larger families.
Keywords: I2; J1; 330; birth order; family size; human capital